THE ROLE OF VILLAGE GOVERNMENT IN IMPROVING COMMUNITY DEVELOPMENT AND WELFARE IN TABA SATING VILLAGE, TEBAT KARAI DISTRICT, KEPAHIANG REGENCY - Yoki Wijaya; Maria Ekowati (Media Inovasi Pendidikan dan Publikasi, 2026)
Village development and improving community welfare are the main goals of implementing village government. However, its implementation still faces various obstacles such as limited resources, not yet optimal implementation of development programs, and varying levels of community participation. This condition is a challenge for the Taba Sating Village Government in realizing equitable and sustainable development. This research aims to determine and describe the role of the Taba Sating Village Government in implementing development and its efforts to improve the welfare of the research community using a qualitative approach with the research location in Taba Sating Village, Tebat Karai District, Kepahiang Regency. Data was obtained through observation, interviews with village heads, village officials and the community, as well as documentation in the form of archives and village activity reports. The data was analyzed descriptively through the stages of data collection, data reduction, data presentation and drawing conclusions. The results of the research show that the Taba Sating Village Government has carried out its role through development planning, managing village funds, building facilities and infrastructure, community empowerment, and improving public services. The various programs implemented have had a positive impact on people's lives, especially in supporting economic activities and increasing access to public facilities. The village government also involves the community in the development process through village meetings so that residents' aspirations can be accommodated well even though there are still several obstacles, such as limited resources and unequal community participation. Better cooperation is needed between the village government and the community so that development and increasing welfare can be achieved optimally. and sustainable.